Azobenzene protonation as a tool for temperature sensing - Antti Siiskonen; Sami Vesamäki; Arri Priimagi (Beilstein Journal of Organic Chemistry)
Azobenzenes can be protonated at one of the azo nitrogen atoms, leading to significant changes in their absorption and photochemical properties. While azobenzene protonation has been recently used as a tool in photoswitching studies, the factors influencing protonation itself have received little attention. Here, we report a strong temperature dependence of azobenzene protonation in 1,2-dichloroethane and highlight its potential for temperature sensing applications. Density functional theory calculations were performed to support our findings and to investigate the mechanisms of azobenzene–acid interactions, aiming to guide the design of azobenzene-based temperature sensors in future research.